Model Pembelajaran PKn Berbasis Multikulturalisme untuk Siswa Sekolah Dasar - Liandy, Septian (Al-Mafahim: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This study aims to develop a multiculturalism-based Civics Education (PKn) learning model for elementary school students to foster tolerance and national unity in Indonesia’s diverse society. Using a library research method with a qualitative approach, the research analyzes academic literature, including journal articles, books, and policy documents, focusing on multicultural education and PKn learning models. Data were collected through systematic searches on academic databases (Google Scholar, ERIC, DOAJ) and analyzed using thematic and content analysis techniques. The results indicate that a multicultural approach in PKn learning, supported by experiential methods and digital technology, significantly enhances students' understanding of diversity and promotes inclusive attitudes. However, challenges such as limited teacher training and resources remain. The study concludes that integrating multicultural values into PKn requires collaborative efforts among educators, schools, and policymakers to create an inclusive and adaptive learning environment.